Dental Service Utilization among Urban and Rural Older Adults in China – A Brief Communication - Bei Wu, PhD (Blackwell Synergy, 2007)
China’s health care system is bifurcated in nature between rural and urban areas. In addition, there is a huge gap in socioeconomic status between rural and urban residents.